Large electric field-induced strain and large improvement in energy density of bismuth sodium potassium titanate-based piezoelectric ceramics - Supalak Manotham (2018)
© 2017 Elsevier B.V. Ceramic solid solutions based on (1-x)Bi0.5(Na0.84K0.16)0.5TiO3-xBa(Nb0.01Ti0.99)O3or (1-x)BNKT-xBNbT) (where x = 0, 0.01, 0.03, 0.05 and 0.07 mol fraction) were investigated to demonstrate the improvement of electrical properties as compared to the unmodified BNKT ceramic. The dielectric, ferroelectric, piezoelectric and electric field-induced strain properties were investigated as a function of composition and temperature. All ceramics presented a single phase perovskite structure. X-ray diffraction analysis revealed a transition from co-existing rhombohedral-tetragonal phases to a single tetragonal phase for compositions with x > 0.03. The maximum dielectric constant tended to increase with increasing BNbT content and the dielectric spectra for all compositions exhibited a broad maximum around Tdand Tm. The polarization hysteresis measurement indicated a disruption in the long range ferroelectric order at the critical composition of x = 0.03 along with a significant enhancement in the electric field-induced strains (Smax= 0.41%) with a large normalized strain coefficient (d*33= Smax/Emax) of 683 pm/V. The x = 0.03 composition also presented a high energy density (0.67 J/cm3) as compared with the unmodified BNKT composition (0.25 J/cm3). These results suggest that the (1-x)BNKT-xBNbT solid solution is a promising lead-free piezoelectric material candidate.